Least Significant Braille Method in Steganography Using Digital Image Media For Security Message - Megah Mulya; Zikry Sugiwa (Universitas Sriwijaya, 2017)
Confidentiality of the message or the information is the most important and essential. It is very influential on the party who has the valuable message when they want to exchange messages on others. To keep the message is not known to others, the necessary security on the message. Steganography is one technique for providing security to the message. Steganography is a technique to hide messages in a medium, such as pictures, sounds, and video. Steganographic technique used in this study is the Least Significant Braille (LSBraille). This technique makes use of human vision in the message on the bit value was not significant. This study focuses on how much resistance level stego image to various image processes and measure results accuracy Peak Signal to Noise Ratio (PSNR). From the result of the insertion of a secret message, that the level of resistance stego image is not resistant to digital image processing. The result of the calculation of PSNR value obtained from experiments on all data samples between 51-73 dB